Financial management audits for school quality improvement in Indonesia: A comprehensive literature review - Dahlan; M. Anas; Listiana Sri Mulatsih; Alfiana; Abdul Kadir Ahmad (UIN Raden Mas Said Surakarta, 2024)
The purpose of this study is to examine financial management audits of educational institutions to improve the quality of schools in Indonesia. This literature review involves several key steps: identifying and narrowing the research topic; searching for relevant literature sources including books, articles, journals, and other documents; reading and understanding the contents of these sources; compiling and analysing the collected data; and finally, drawing conclusions from the research. This study's findings underscore the critical importance of financial audits for educational institutions in ensuring compliance with laws and regulations, enhancing transparency and accountability, boosting the efficiency and effectiveness of financial management, preventing fraud, and securing the sustainability of these institutions. Financial audits serve a crucial role in the improvement of educational quality in Indonesia by fostering accountability and transparency in budget usage. Regular audits require institutions to meticulously account for financial transactions, mitigate the risk of fund misuse, and promote effective fund allocation. This suggests that bolstering financial audit practices in Indonesian educational institutions can significantly elevate educational standards.